Unlocking Consumer Preferences: Sensory Descriptors Driving Greek Yogurt Acceptance and Innovation - Helena Maria Andre Bolini; Flavio Cardello; Alessandra Cazellatto de Medeiros; Howard Moskowitz (Foods)
Greek yogurt, a traditional food with roots in Ancient Greece, Mesopotamia, and Central Asia, has become a dietary staple worldwide due to its creamy texture, distinct flavor, and rich nutritional profile. The contemporary emphasis on health and wellness has elevated Greek yogurt as a functional food, recognized for its high protein content and bioavailable probiotics that support overall health. This study investigates the sensory attributes evaluated by a panel of 22 trained assessors and the consumer preferences driving the acceptance of Greek yogurt formulations. Samples with higher consumer acceptance were characterized by sensory attributes such as “high texture in the mouth, surface uniformity, creaminess, apparent homogeneity, mouth-filling, grip in the mouth, ease of pick-up with a spoon, milk cream flavor, sweetness, and dairy flavor” (Tukey’s test, p < 0.05). These attributes strongly correlated with consumer preferences, underscoring their importance in product optimization. The findings provide a framework for refining Greek yogurt formulations to address diverse market demands, achieving a balance between sensory excellence and practical formulation strategies. This research reinforces the significance of Greek yogurt as a culturally adaptable, health-promoting dietary component and a promising market segment for ongoing innovation.